Efektyvių projektų kūrimo demonstracinė sistema - Ambrasas, Gintautas; Kaklauskas, Artūras; Zavadskas, Edmundas K. (Journal of Civil Engineering and Management, 1996)
Demonstration system for development of efficient projects The paper describes the Demonstration System suggested by the authors. This Demonstration System enables efficient performance of alternative life-time process planning, multicriteria assessment, utility degree determination and selection of the most efficient versions of various projects and their constituent parts: • Determination of rational design solutions for walls, windows, roof structures, basement floor, heating system. • Selection of rational constituent parts of a project (selection of construction site and location, multipurpose complex assessment of buildings, determination of rational types of contracts). • Selection of efficient interested parties (contractors, suppliers, neighbours). • Alternative designing of life-time process of a project (one-family dwelling houses; agricultural, cast-in-place, prefabricated panel, and thermal renovation of buildings), its multicriteria assessment, determination of utility degree and selection of the most efficient version: • Determination of efficient investment projects. • Preparation of recommendations on efficiency increase of projects. • Alternative roof-to-basement designing of a building (one-family dwelling houses; agricultural, cast-in-place, prefabricated panel, and thermal renovation of buildings) and its multicriteria analysis. This Demonstration System enables to perform alternative designing of projects and their constituent parts, multicriteria analysis, determination of utility degree and priority and preparation of recommendations on further improvement of projects. The Demonstration System is composed of two main parts: knowledge and decisionmaking subsystem. The knowledge base contains information (system and subsystems of criteria, values and significance of criteria, etc.) fully characterizing life-time processes of various projects (investments, buildings and so forth) and their constituent parts. For instance, knowledge base of life-time process of constituent parts of a building consists of information on alternative construction sites, buildings, designers, contractors, suppliers and so on. A construction site can be described by the following system of criteria: cost, assessment of existing services (water supply, sewerage, gas, electric power supply), air contamination level, living expenses, shopping possibilities, assessment of possibilities for recreation, sports and medical care, possibility to find a job, development outlooks of the district, transport conveniences, etc. The composed knowledge base is processed in various sections by decision-making subsystem. The multicriteria analysis of received results is performed by decision-making subsystem two. The Demonstration System is used by Bachelors, Engineers and Masters while working on their term and final projects. The paper gives a more detailed analysis of the proposed System. There is presented one of works performed by means of the Demonstration System. Article in Lithuanian. First Published Online: 26 Jul 2012